Mental illness and criminal behavior - Fiack, Shannon (At issue Crime)
Mental illness and substance abuse increase the risk of violence / Richard A. Friedman, M.D -- There is a relationship between schizoid personality disorder and violence / Wagdy Loza and Samia Hanna -- Mental illness and crime cannot be compared due to varying definitions / Herschel Prins -- Criminals know right from wrong, regardless of mental illness / Stanton E. Samenow, Ph.D -- Violent people should be treated as criminals rather than as patients / Dr. Peter Breggin -- The mentally ill are warehoused in prisons due to inadequate health services / William Kanapaux -- Psychiatric hospitals are not equivalent to prison / Joanmarie Ilaria Davioli -- Mentally ill prison inmates need special treatment / Kenneth Adams and Joseph Ferrandino -- The mentally ill are mishandled by the justice system / ACLU -- The not guilty by reason of insanity plea should remain valid / Mental Health America -- Insanity should be a medical, not a legal, determination / Dirk Olin -- Television shapes views of mental health and crime / Rachel Gans-Boriskin, Claire Wardle